PEMBINAAN OLAHRAGA TINJU AMATIR DI SASANA DELTA BOXING CAMP KABUPATEN TEGAL DAN SASANA PERTINA KOTA TEGAL TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The background of this research there is a problem on the coaching done in Sasana and Tegal regency . The purpose of this study was to determine the amateur sport coaching in Boxing Camp Delta Sports Camps and Sports Camps Pertina Tegal Tegal in 2013 . This research uses qualitative research . The method used survey methods using techniques of observation , interview and documentation. The conclusions obtained are boxing coaching pattern implementation constraints. Organization has not been going well . Facilities and infrastructure need for the addition . Funding comes mostly from KONI . Training programs have been conducted in accordance with existing programs . Coach certified . Less than the maximum recruitment of athletes . Achievement is good enough